Alteration in the phosphorylation status of NMDA receptor GluN2B subunit by activation of both NMDA receptor and L-type voltage gated calcium channel. (14th September 2019) - Kumar, Mantosh; John, Mathew; Madhavan, Mayadevi; James, Jackson; Omkumar, Ramakrishnapillai V.
Highlights: Regulation of NMDA receptor GluN2B-Ser 1303 phosphorylation studied in vivo . Activation of L-type voltage gated calcium channel and NMDA receptor both cause increase in phospho-GluN2B-Ser 1303 . Effects of both NMDA receptor and L-type voltage gated calcium channel are mediated through CaM kinases. Phospho-GluN2B-Ser 1303 is under dynamic regulation by phosphatases and kinases. Abstract: Calcium influx through N-methyl-D-aspartate receptors (NMDAR) and voltage-gated calcium channels (VGCC) play major roles in postsynaptic signaling mechanisms. NMDAR subunit GluN2B is phosphorylated at Ser 1303 . Phosphorylation at this site is a prominent event in cell culture systems as well as in vivo . However, the functional significance of phosphorylation at this site is not completely understood. In this study, we compared the effect of calcium signaling through NMDAR and VGCC on the phosphorylation status of GluN2B-Ser 1303 in the rat in vivo . VGCC was activated by intraperitoneal (IP) injection of the activator, BayK8644 and NMDAR was activated by intracerebroventricular (ICV) injection of NMDA in separate experimental groups. We found that the level of phospho-GluN2B-Ser 1303 in the cortex and in the hippocampus increased in response to activation of either channel. The effects could be prevented by prior ICV administration of the specific blockers of these channels such as MK-801 for NMDAR and nifedipine for VGCC. The effect was also blocked by pretreatment with ICV administration of KN-93 indicating that it is mediated through CaM kinase. Both during NMDAR activation and VGCC activation, cell survival associated signals such as phospho-AKT and phospho-CREB showed decrease, consistent with activation of cell death pathways during these treatments. We conclude that under in vivo conditions, calcium influx through either NMDAR or VGCC activates CaM kinase, which in turn phosphorylates GluN2B-Ser 1303 .